Isolation and Identification of Ten Genera of Plant Parasitic Nematodes - Rahman, MM; Mian, IH (Bangladesh Journal of Scientific and Industrial Research, 2010)
A study was undertaken to isolate and identify different genera of plant parasitic nematodes from soil and plant samples during July to October 2007 in the Laboratory of Plant Pathology at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, Bangladesh. Altogether 10 (Ten) nematodes belonging to 10 genera were isolated and identified from various soil and plant samples. For identification of plant parasitic nematodes, stylet and other anatomical structures such as Dorsal esophageal Gland Orifice (DGO), Esophageal lumen, Median bulb, Basal bulb, Intestine, Reproductive structures (vagina and its position, specula ) Tail types etc. were used as main criteria. Among 10 (ten) different identified genera of nematodes (Criconemoids sp., Hemicriconemoides sp., Tylenchus sp., Ditylenchus sp., Tylenchorhynchus sp., Hoplolaimus sp., Helicotylenchus sp., Pratylenchus sp., Meloidogyne sp., Radinaphelenchus sp.) maximum nematodes were under the family of Tylenchidae. The abundance numbers of plant parasitic nematodes were found as the Ditylenchus sp.(Ufra nematode) and Meloidogyne sp.(Root knot nematode) which were the serious plant pathogens causing ufra in rice and root knot in different crops respectively, so far recorded in Bangladesh. Key words: Isolation; Identification; Plant parasitic nematodes. DOI: 10.3329/bjsir.v45i3.6536 Bangladesh J. Sci. Ind. Res. 45(3), 267-270, 2010